The Development Of Reading Ability On Vocabulary With Final Consonants According To Their Sections By Multi-Sensory Of Orton-Gillingham Teaching Method : Case Study Of Second Grade Students With Learning Disability - bunpreecha, kanokwan; Jamsai, Pattaraporn (Mahachula Academic Journal, 2024)
This study aims to study the development of the ability to read on vocabulary with final consonants according to their sections by multi-sensory of Orton-Gillingham teaching method. The target group was three students with learning disability who were studying in second grade. The instruments of this study were (1) the learning activity plan and (2) the word reading test. The data was analyzed by percent. The findings indicated that after using the multi-sensory with Orton-Gillingham teaching method, the target group had score on vocabulary reading ability higher than pretest. In adiition, the progress precentage increased by 45 percent. This study showed that teaching students to read vocabulary with final consonants according to their sections by multi-sensory of Orton-Gillingham teaching method can improve target group in reading ability.